Matematica 3 H
Matematica 3 H
Matematica 3 H
2
│ x −2 x−3 │
I) 1− + +4 0
2
2 x +│ x −4 x +4 │+1 √8−x +1
Del teorema:
√a + √b ≤ 0 ↔ a = 0 ⋀ b = 0
|x 2−2 x−3|
1) 1- =0
2 x +|x 2−4 x+ 4|+1
|x 2−2 x−3|
=1
2 x +1+|x 2−4 x+ 4|
a) (−x +3 ) (−x−1 ) = ∞ 2- 2x + 5
x - 2x - 3 = x – 2x +5
2 2
-3 ≠ 5
Sa = φ
b) (−x +3 ) ( x+1 ) = x 2 – 2x + 5
- x 2 + 2x + 3 = x 2 – 2x + 5
0¿ 2 x 2 – 4x + 2
0 = x 2 – 2x + 1
0 = ( x−1 )2
X=1 ⇒ Sb: { 1 }
c) ( x−3 )( x +1 ) = x 2 – 2x + 5
x – 2x - 3 = x – 2x + 5
2 2
-3 ≠ 5
Sc = φ
2)
2+ √ x 2−8 x +12
=0
√ 8−x +1
a¿8 – x ≥ 0
X≤8 ⇒ x1,ϵ¿
b) x 2 – 8x + 12 ≥ 0
( x−6 )( x−2 ) ≥ 0
x≥6 ⋀ x≥ 2
x≥6 ⇒ x2, ϵ{ [ 6 ; + ∞ ⟩
S2 = { x 1 ∩ x 2 } = [ 6 ; 8 ]
S1 ∩ S2 = [ 1 ] ∩ [ 6 ; 8 ]
CS = φ